2016
DOI: 10.1590/s1984-29612016064
|View full text |Cite
|
Sign up to set email alerts
|

First isolation of Dioctophyme renale eggs from an urban environment and identification of those from animal urine

Abstract: Dioctophyme renale is a zoonotic parasite with worldwide distribution, although its occurrence is little known. The objective here was to evaluate the presence of parasite eggs in the environment and in the urine of dogs and cats in an urban area. Soil samples and urine were evaluated respectively by means of the Caldwell-Caldwell technique and urinalysis. Out of the 100 soil samples, 3% presented D. renale eggs, and out of the 43 urine samples, 18.6% were positive, including the feline samples. Thus, D. renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
(6 reference statements)
0
5
0
2
Order By: Relevance
“…Perera et al (3), utilizando a técnica de Caldwell e Caldwell, analisaram amostras ambientais de areia, na região de uma clínica veterinária no município de Pelotas, onde muitos Ferraz A, Pires BS, Evaristo TA, Perera SC, Nizoli LQ, Rapetti JCS. Técnica para identificação de ovos de Dioctophyme renale em urina de gatos, empregada em sílica.…”
Section: Resultados E Discussõesunclassified
See 1 more Smart Citation
“…Perera et al (3), utilizando a técnica de Caldwell e Caldwell, analisaram amostras ambientais de areia, na região de uma clínica veterinária no município de Pelotas, onde muitos Ferraz A, Pires BS, Evaristo TA, Perera SC, Nizoli LQ, Rapetti JCS. Técnica para identificação de ovos de Dioctophyme renale em urina de gatos, empregada em sílica.…”
Section: Resultados E Discussõesunclassified
“…Os hospedeiros definitivos, seja estes, cães, gatos, animais silvestres ou o homem, eliminam os ovos de D. renale na urina, contaminando o meio ambiente (3). O ciclo possui um período de incubação em meio aquático, onde os ovos são ingeridos pelo hospedeiro intermediário, o anelídeo oligoqueta, e se tornam desta forma infectantes (4).…”
Section: Introductionunclassified
“…There have been several cases of animals parasitized by D. renale in the Pelotas region (Rappeti et al, 2017). Eggs of this parasite were found in soil samples from the urban region of the city (Perera et al, 2017a), and third-stage larvae were found in 50% (n = 60) of the specimens of the turtle D'Orbigny's slider (Trachemys dorbigni) that were evaluated (Mascarenhas & Müller, 2015). These surveys show that dioctophymosis is present and disseminated in Pelotas, thus favoring infection with large numbers of worms.…”
Section: Introductionmentioning
confidence: 99%
“…Although urinalysis is not the only recommended way of diagnosing dioctophymosis, Perera et al [26] observed that 18.6% of urine samples in dogs and cats were infected by the helminth, which highlights the importance of this test for the diagnosis of parasitic infections.…”
mentioning
confidence: 99%
“…Moreover, eggs were found in the urine of Patient 2, which occurs when a sexually mature D. renale female is found in the kidney [ 23 ]. Although urinalysis is not the only recommended way of diagnosing dioctophymosis, Perera et al [ 26 ] observed that 18.6% of urine samples in dogs and cats were infected by the helminth, which highlights the importance of this test for the diagnosis of parasitic infections.…”
mentioning
confidence: 99%